Canine filariasis in the Amazon: Species diversity and epidemiology of these emergent and neglected zoonoses. - Emanuelle Gabriela Gualberto de Argôlo; Thais Reis; Diego Ari Teixeira Fontes; Evonnildo Costa Gonçalves; Elane Guerreiro Giese; Francisco Tiago de Vasconcelos Melo; Jeannie Nascimento Dos Santos; Adriano Penha Furtado (PLoS ONE, 2018)
Dirofilaria immitis and Acanthocheilonema reconditum are common parasites in dogs but have also been reported parasitizing humans. The differential diagnosis and epidemiological evaluation of these zoonoses are important to the development of efficient public health policies and control strategies. The purpose of this study was to carry out an epidemiological survey by using molecular methods for the specific identification of filarid parasites of domestic dogs in the Marajó mesoregion, State of Pará (PA), Brazil. A total of 418 canine blood samples from Marajó mesoregion (Northern Brazil) were collected, submitted to DNA extraction, polymerase chain reaction (PCR) with "pan filarial" primer, subsequent sequencing and sequence analysis using BLASTn software comparison with previously deposited sequences in GenBank. After that, a phylogenetic analysis by Maximum Parsimony was performed to aid the specific diagnosis. The obtained sequences showed the occurrence of 9 (2.15%) dogs infected with D. immitis and 30 (7.18%) by A. reconditum, with a confidence interval of 95%, there were no cases of co-infection. We observed that male dogs were more likely to D. immits and A. reconditum infection. However, age was not significant to both infections. This study reports for the first time the occurrence of A. reconditum in the northern region of Brazil and confirmed the presence of D. immitis in the Marajó mesoregion.